2019
DOI: 10.1155/2019/5308014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of Beddington–DeAngelis Predator‐Prey System with Nonlinear Impulse Feedback Control

Abstract: In this paper, a predator-prey system with pesticide dose-responded nonlinear pulse of Beddington–DeAngelis functional response is established. First, we construct the Poincaré map of the impulsive semidynamic system and discuss its main properties including the monotonicity, differentiability, fixed point, and asymptote. Second, we address the existence and globally asymptotic stability of the order-1 periodic solution and the sufficient conditions for the existence of the order-k(k ≥ 2) periodic solution. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Many studies devote to the properties of periodic solutions [17][18][19][20], including the existence, stability and periodicity, etc. It has been confirmed that the Poincaré map is a very useful tool to prove the existence of periodic solution in state-dependent impulsive differential equations [21][22][23]. In addition, Simeonov and Bainov [24] gave analogue of Poincaré criterion in ref.…”
Section: Introductionmentioning
confidence: 90%
“…Many studies devote to the properties of periodic solutions [17][18][19][20], including the existence, stability and periodicity, etc. It has been confirmed that the Poincaré map is a very useful tool to prove the existence of periodic solution in state-dependent impulsive differential equations [21][22][23]. In addition, Simeonov and Bainov [24] gave analogue of Poincaré criterion in ref.…”
Section: Introductionmentioning
confidence: 90%
“…For a herbivore-plankton model with cannibalism, the existence and stability of order-1 periodic solution were discussed in [9], where the model was a system of Impulsive Differential Equations (IDEs), which has more complex and abundant dynamics, but can fully take into account the impact of instantaneous mutations on the state and more deeply reflect the law of things changing. IDEs are widely used in biology, medicine, control theory and other fields [10][11][12][13]. In biology, the impulsive differential equation can be proposed to incorporate the possible changes in the population into the research model, more information can be found from [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, threshold state pulsed dynamic systems have been widely used [7][8][9][10][11][12][13][14]. e geometric theory of impulse dynamical system has been well-developed [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%